PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENGGUNAAN MEDIA BELAJAR BERBASIS TEKNOLOGI WORDWALL DI KELAS V SD NEGERI 241 PALEMBANG - Linda Agusti; Yenny Anwar (JURNAL ILMIAH NUSANTARA, 2025)
One of the subjects that students do not interest is mathematics. Several factors that cause this case, one of which is the monotonous learning process so that students feel that mathematics is a difficult and boring subject. This research is a type of Classroom Action Research (CAR) that has purpose at identifying of improving student learning outcomes in Mathematics subjects by using wordwall media in class V at SD Negeri 241 Palembang. There are 28 students in class V.A who are the subjects of the study, consisting of 15 females and 13 males. Data collection was carried out by observation, tests, and documentation. For this study, two cycles were carried out, in which each cycle showed differences in the learning outcomes that students displayed in the learning process before and after using wordwall media. Based on this study, the results obtained were that the application of technology-based learning media "wordwall" can improve student learning outcomes in mathematics subjects and create a pleasant atmosphere during the learning process in class V.A SD Negeri 241 Palembang.